If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xy + -7x = y + 6 Reorder the terms: -7x + yX = y + 6 Reorder the terms: -7x + yX = 6 + y Solving -7x + yX = 6 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1yX' to each side of the equation. -7x + yX + -1yX = 6 + y + -1yX Combine like terms: yX + -1yX = 0 -7x + 0 = 6 + y + -1yX -7x = 6 + y + -1yX Divide each side by '-7'. x = -0.8571428571 + -0.1428571429y + 0.1428571429yX Simplifying x = -0.8571428571 + -0.1428571429y + 0.1428571429yX
| 6x+9y=4500 | | (1.59+x)-2.78=.5 | | (1.59+x)-2.78=2.5 | | 3n-15=180 | | 4x+126=-18-2(x-66) | | 326=16t^2 | | 63h-7w=800 | | 87.8=16t^2 | | 3x+2=-6x | | 4x+20=5x-17 | | (-2)+6=n | | 3x+2=-6-3 | | 4=(-2)-k | | x^4-2x^3-7x^2-2x+1=0 | | -2-6=n | | -5x-7=2m+6 | | ln(x+6)+ln(x)=0 | | 5x+12+3x=180 | | graphx+6y=30 | | (-2)-6=N | | 0.70x+0.35(110)=0.35(66) | | V-2=-5(39-V)-3 | | 150=10x+30 | | -3(4-4b)-6b=5(b-1) | | (-2)+-6=N | | 2.4x-7.96=7.4 | | y^2+6y-8= | | y=2x-5+1 | | 1n(x+2)-1n(x)=1 | | 10x+6-6x-3= | | -5(3+4n)=-2(6n-7)-5 | | (5)2y-1= |